Clindamycin-associated enterocolitis in guinea pigs: evidence for a bacterial toxin. - Knoop, F C (1979)
Experimental enterocolitis was induced in guinea pigs by intraperitoneal injection of clindamycin. Specimens of feces were collected daily in phosphate-buffered saline (pH 7.0) and pooled every second day. The pooled samples were centrifuged to remove solids, and the supernatant was sterilized by membrane filtration. The sterile fecal supernatants were then dialyzed for 48 h against two 15-liter changes of phosphate-buffered saline and subsequently tested for toxicity in cultured monolayers of mouse adrenal cells. A filterable toxin(s) was found in the fecal supernatants on days 2, 4, and 6 postchallenge and not in pretreatment samples. The toxin(s) caused enterocolitis when administered orogastrically to healthy animals and altered the morphology of cultured mouse adrenal cells. The alteration of adrenal cell morphology was neutralized by specific antitoxin to Clostridium histolyticum.